Tinjauan Produksi Pala di Sumatra Barat Berdasarkan Lahan Produktif Menggunakan Pemulusan Eksponensial dan Diikuti dengan - Rifa’atul Hamda; Helma Helma (Journal of Mathematics UNP, 2020)
Abstract – The nutmeg production of West Sumatra since 2011-2018 has decreased fluctuately, so that influenced society economi. The purpose of this research was to know the model and nutmeg production prediction result for the next time, also to know wich regency/town are not exploit the land optimally. The method that used was Tripel Exponential Smoothing Brown with parameter a and Profile Analysis. When determining parameter a, the Mean Square Error is used. While profile analysis was determined by comparing amount of product of land area with amount of nutmeg production, so that used parallelism test, coincidance, and level. The data that used was secondary data which it was obtained Central Static Agency publication of West Sumatra 2012-2019. The nutmeg prediction result at 2019-2023 sequentially in tonnes are 1255.95, 1261.38, 1266.94, 1272.65 and 1278.49. Here are some region that are not optimal yet, among them: Mentawai Island Regency, South Pesisir, Padang Pariaman, and Padang City. Keywords – total production nutmeg, triple exponential smoothing brown type, profile analysis.